2021
DOI: 10.3390/rs14010040
|View full text |Cite
|
Sign up to set email alerts
|

Few-Shot Learning for Post-Earthquake Urban Damage Detection

Abstract: Among natural disasters, earthquakes are recorded to have the highest rates of human loss in the past 20 years. Their unexpected nature has severe consequences on both human lives and material infrastructure, demanding urgent action to be taken. For effective emergency relief, it is necessary to gain awareness about the level of damage in the affected areas. The use of remotely sensed imagery is popular in damage assessment applications; however, it requires a considerable amount of labeled data, which are not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 32 publications
(88 reference statements)
0
1
0
Order By: Relevance
“…In [9] a few-shot learning technique from [50] was used in order detect complex morphologies representing poor areas within the urban environment, the authors found out that the technique works very well when only a hand-full of samples are available. Other approaches have been using selfsupervised embedding optimization for adaptive generalization in urban settings [51] or using Prototypical Networks for urban damage detection after natural hazards [52].…”
Section: Transfer-learning From Few Samplesmentioning
confidence: 99%
“…In [9] a few-shot learning technique from [50] was used in order detect complex morphologies representing poor areas within the urban environment, the authors found out that the technique works very well when only a hand-full of samples are available. Other approaches have been using selfsupervised embedding optimization for adaptive generalization in urban settings [51] or using Prototypical Networks for urban damage detection after natural hazards [52].…”
Section: Transfer-learning From Few Samplesmentioning
confidence: 99%